Analysis of the Implementation of PSAK 109 and PSAK 112 at the National Zakat Management Institution (LAZNAS) Yatim Mandiri Kepanjen Malang - Inayah, Khoirotul; Ashari, Muhammad Hasyim (Nomico, 2024)
The purpose of this study is determine application of PSAK 109 about Zakat, Infaq/Sadaqah Accounting, and PSAK 112 about Waqf Accounting at LAZNAS Yatim Mandiri Branch Kepanjen about recognition, the measurement, presentation and disclosure that Zakat, Infaq/Sadaqah, and Waqf (ZISWAF). This research is a qualitative study with a descriptive approach. Data collection methods use in this study were interviews, observation, and documentation. The result showded at LAZNAS Yatim Mandiri branch Kepanjen have implemented about recognition, the measurement, presentation, but not implemented about disclosure of PSAK 109 about Zaqat, Infaq/Sadaqah Accounting. In addition LAZNAS Yatim Mandiri branch Kepanjen have implemented about recognition, the measurement, but not implemented about presentation and disclosure of PSAK 112 about Waqf Accounting.